2006
DOI: 10.4321/s1885-642x2006000200007
|View full text |Cite
|
Sign up to set email alerts
|

Como medir (o no medir) la adhesión en el tratamiento de erradicación

Abstract: This study aimed to test a novel method of compliance measurement in Portuguese community pharmacy in Helicobacter pylori patients. A case series design was used where compliance indicators were electronically measured, aside with patients' reports. Experienced adverse drug reactions, perceived benefit of therapy and quality of life were also measured. Mean compliance proportion was 56% and a positive impact on patients' perceived health status was found. The method used was welcomed by community pharmacists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In our study, patients with peptic ulcer disease had poor medication adherence, in agreement with data from previous studies (22). A possible explanation could be the metallic taste of medications used to eradicate Helicobacter pylori infection, as reported in previous research (23). Another reason could be the frequency of drug administration, the number of pills administered, and the complexity of eradication regimens, explaining the inverse relationship between the number of doses and adherence (24).…”
Section: Diseases and Medication Adherencesupporting
confidence: 90%
“…In our study, patients with peptic ulcer disease had poor medication adherence, in agreement with data from previous studies (22). A possible explanation could be the metallic taste of medications used to eradicate Helicobacter pylori infection, as reported in previous research (23). Another reason could be the frequency of drug administration, the number of pills administered, and the complexity of eradication regimens, explaining the inverse relationship between the number of doses and adherence (24).…”
Section: Diseases and Medication Adherencesupporting
confidence: 90%
“…Patients with poor medication compliance is another key influencing factor of H. pylori treatment failure (Jaka et al, 2019; Lan et al, 2022; Osipenko et al, 2014; Shawky et al, 2022). Surprisingly, a growing body of recent studies suggested that pharmacists' participation in the process of H. pylori treatment could not only increase patients' medication compliance, but also reduce the treatment costs and improve clinical outcomes for patients (Al‐Eidan et al, 2002; Martins et al, 2006; Seko et al, 2019; Sun et al, 2020). Pharmacists should actively participate in the management practice of H. pylori eradication therapy, and provide individualized medication education to patients in hospitals or at home, so as to give full play to the social value of pharmacists (L. C. Li, Chen, et al, 2021; L. C. Li, Han, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…pylori patients' perceived health status by using electronic recording devices (Martins et al, 2006). A hospital in Japan investigated 452 patients infected with H. pylori who were managed by pharmacists from January 2015 to December 2017, and found that the medication guidance provided by pharmacists could improve the quality of life and H. pylori eradication rate (91.4%) though the pharmacists incurred additional labor costs (Seko et al, 2019).…”
Section: Medication Compliance In H Pylori Treatment Managementmentioning
confidence: 99%
See 2 more Smart Citations